Nâng cao khả năng nghe hiểu cho sinh viên thông qua sử dụng các video thực - Mai, Lan Anh (Tạp chí Thiết bị Giáo dục, 2023)
Listening is undoubtedly an indispensable skill during the process of foreign language learning. It is also one of the critical factors greatly influencing the success or failure of a language learner. There is no denying that using authentic videos is beneficial to boosting students' interests and enhancing their listening comprehension. The aim of the study is to demonstrate the effectiveness of using the video resources on listening improvement, in addition to proposing some criteria for selecting the kind of materials which is of great help in teaching listening comprehension.